Markov Analysis of Water Discharge as an Indicator of Surface Water Security of the Bandung Basin - Wulandari, S.; Sabar, A.; Setiadi, T.; Kurniawan, B. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Water security is the fulfillment of access to adequate and sustainable water needs (quantity and quality) for the growth of human and ecosystem life and the ability to reduce risks associated with water. By knowing the water security of an area, efforts to conserve, utilize, control destructive force, develop information systems and participate in the community can be assessed to what extent and how the management has been carried out. The purpose of this research is to formulate the amount of water availability per capita (quantity) of surface water and to determine the quantity of the worst water quality at a critical time (the worst quantity) to be used as a reference in determining the amount of water resistance for development. The only observed water quality was the BOD (Biological Oxygen Demand) organic pollutant value in the dry year in the dry season using the Markov Chain Method. Water security in the Bandung Basin is currently classified as bad (rare) because the water availability index figures only indicate 174 m3 per capita per year (quantity). Meanwhile, data on the quality value of BOD (Biological Oxygen Demand) pollutants in dry years (R5) of 129 mg/l and very dry years (R10) of 112 mg/l which has also exceeded the class I quality standard of PP No. 22/2021 ( 2 mg/l) regarding water quality management and pollution control which is designated for raw water needs drinking water. Changing water use patterns and promoting effective implementation of integrated water resources management are essential strategies for increasing water security in Indonesia.